2008
DOI: 10.1677/erc-07-0271
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a dopamine-somatostatin chimeric molecule, BIM-23A760, in the control of cell growth from primary cultures of human non-functioning pituitary adenomas: a multi-center study

Abstract: Dopamine D2 and somatostatin receptors (sstrs) were reported to affect non-functioning pituitary adenoma (NFPA) proliferation in vitro. However, the reported results differ according to the experimental conditions used. We established an experimental protocol allowing reproducible evaluation of NFPA cell proliferation in vitro, to test and compare the antiproliferative effects of dopamine and somatostatin analogs (alone or in combination) with the activity of the dopamine-somatostatin chimeric molecule BIM-23A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 59 publications
9
89
0
2
Order By: Relevance
“…The mean D 2 mRNA level was similar to that found in pituitary GH and gonadotroph tumors , Florio et al 2008) but was clearly higher than that of the GEP-NETs. Previous studies have shown the presence of D 2 in normal adrenal medulla and PCC by northern blot (Pupilli et al 1994, Wu et al 2001, by RT-PCR (Wu et al 2001), or by RT-PCR, immunohistochemistry, and ligand binding studies (Pivonello et al 2004).…”
Section: Discussionsupporting
confidence: 74%
“…The mean D 2 mRNA level was similar to that found in pituitary GH and gonadotroph tumors , Florio et al 2008) but was clearly higher than that of the GEP-NETs. Previous studies have shown the presence of D 2 in normal adrenal medulla and PCC by northern blot (Pupilli et al 1994, Wu et al 2001, by RT-PCR (Wu et al 2001), or by RT-PCR, immunohistochemistry, and ligand binding studies (Pivonello et al 2004).…”
Section: Discussionsupporting
confidence: 74%
“…SDF1 effect on cell proliferation was studied in eight primary cultures of human pituitary adenomas [two GHomas (GH1 and GH12), one ACTHoma (ACTH1), and five NFPAs (NFPA1, NFPA2, NFPA3, NFPA4, and NFPA6); see Supplementary Table S1B]. Experiments were carried out after magnetic fibroblast deprivation and isolated cells were grown in D-valine containing medium to assure a minimal fibroblast contamination (31). Immunofluorescence experiments done on isolated cells from one adenoma (GH2) showed that all the cells in culture, also expressing CXCR4 and SDF1, are derived from adenomatous tissue because they express GH but not procollagen type I (a marker for fibroblasts; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Single-cell suspensions were seeded (100,000 cells per well) in MEM with low glucose (1 g/L), containing D-valine (Metachem) to avoid fibroblast proliferation, supplemented with 10% FCS, penicillin/streptomycin, and 2.5 Ag/mL amphotericin B (Euroclone; ref. 31).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, dopamine agonists (DA) reduce gonadotropin secretion (14) and inhibit thymidine incorporation in vitro (15), providing a potential therapeutic target for NFPA. However, dopaminergic binding sites (16) as well as D2R mRNA isoforms (17) are less abundant in NFPA than in prolactinomas, perhaps accounting for the modest rate of tumor shrinkage attained by DAs (18).…”
Section: Introductionmentioning
confidence: 99%